Hydrostatic, aerostatic, and hybrid bearing design - Rowe, W. B. (William Brian) (Amsterdam : Elsevier, 2012)
"Compiled for ease of use in practical design scenarios, Hydrostatic, Aerostatic and Hybrid Bearing Design provides the basic principles, design procedures and data you need to create the right bearing solution for your requirements. In this valuable reference and design companion, author and expert W. Brian Rowe shares the hard-won lessons and figures from a lifetime's research and consultancy experience."--P. [4] of cover.
Includes bibliographical references and index.
Keywords: Fluid-film bearings -- Design and construction; Aerostatics